The Application of Diabetes Foot Exercise to Mr. A With Type 2 Diabetes Mellitus as an Improvement of Leg Blood Circulation in the Anturium Room of dr. Soebandi Hospital: Case Study - Dwi Yuni Lestari; Rondhianto; Kushariyadi; Sujarwanto (KHD Production, 2024)
Diabetes mellitus is a metabolic disease characterized by hyperglycemia due to pancreatic cell damage. Diabetes mellitus can lead to various complications such as nephrotic disease, retinopathy, heart disease and stroke, and nerve damage or peripheral neuropathy and other complications, which are also often called diabetic foot. This scientific work uses a case report method that describes the case of Mr. A with the main nursing problem of ineffectiveness. A with the main nursing problem of ineffective peripheral perfusion in the Anturium Room of Dr. RSD. The approach taken is to use comprehensive nursing care for 3 days starting on December 23-25, 2023. In this scientific paper, diabetic foot exercises were applied to Mr. A which can be done for 3 - 4 days. A which can be done for 3 - 4 / week within 15 - 30 minutes with 10 kinds of movements that aim to improve blood circulation in the foot area with the results of research measuring the value of the Ankle Brachial Index (ABI) in Mr. A patient categorized as mild. Mr. A is categorized as mild. Mr. A is categorized as mild with minimal grafting. The application of diabetes mellitus foot exercises is related to improving blood circulation in the feet to prevent diabetes complications.